2017
DOI: 10.1038/npp.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mesolimbic Reward Neurocircuitry in Prevention and Rescue of the Activity-Based Anorexia (ABA) Phenotype in Rats

Abstract: Patients suffering from anorexia nervosa (AN) become anhedonic; unable or unwilling to derive normal pleasures and avoid rewarding outcomes, most profoundly in food intake. The activity-based anorexia (ABA) model recapitulates many of the characteristics of the human condition, including anhedonia, and allows investigation of the underlying neurobiology of AN. The potential for increased neuronal activity in reward/hedonic circuits to prevent and rescue weight loss is investigated in this model. The mesolimbic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 51 publications
4
47
1
1
Order By: Relevance
“…More recently, Foldi et al . () also used the CAV approach in VTA → NAc projection neurons and showed that excitation of this projection increased food intake, ameliorating activity‐based anorexia‐induced weight loss. This CAV–DREADD technique has also been used in other neural pathways.…”
Section: Viral Methods For Chemogenetic Receptor Expressionmentioning
confidence: 99%
“…More recently, Foldi et al . () also used the CAV approach in VTA → NAc projection neurons and showed that excitation of this projection increased food intake, ameliorating activity‐based anorexia‐induced weight loss. This CAV–DREADD technique has also been used in other neural pathways.…”
Section: Viral Methods For Chemogenetic Receptor Expressionmentioning
confidence: 99%
“…Briefly, this approach involves stereotaxically injecting canine adenovirus (CAV), expressing Cre recombinase (CAV‐2‐Cre) into the NAc, which is retrogradely transported to the VTA and recombines with the separately injected activating DREADD virus tagged with a fluorescent reporter [AAV‐hSyn‐DIO‐hM 3 D(G q )‐mCherry], resulting in activation of this neuroanatomically defined pathway. This strategy revealed that the drastic body weight “free‐fall” associated with ABA can be prevented and rescued by reward circuit activation, leading to an increase in food intake and FAA, with a profound increase in survival (Figure ) . The continuation and extension of these targeted studies will directly inform questions about the necessity and sufficiency of the circuitry underpinning ABA and, potentially, the neurobiology of AN.…”
Section: Dopamine and Reward Disruptions In Abamentioning
confidence: 99%
“…Results for (A) and (B) are expressed as mean± SEM ( & P <.01, # P <.001). Reproduced with permission …”
Section: The Activity‐based Anorexia Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, projection‐specific DREADDs expression can be obtained using Cre‐recombinase expressing canine adenovirus. This Cre‐recombinase expressing canine adenovirus is preferentially retrogradely transported to the neuronal somas, where it can interact with the Cre‐dependent DREADDs constructs to express the DREADDs (Boender et al, ; Foldi, Milton, & Oldfield, ; Roelofs et al, ).…”
Section: Introductionmentioning
confidence: 99%